Analysis of chromatin accessibility in peripheral blood mononuclear cells from patients with early-stage breast cancer - Xia, Longjie; Lu, Jiamin; Qin, Yixuan; Huang, Runchun; Kong, Fanbiao; Deng, Yu (Frontiers in Pharmacology, 2024)
Objective: To explore the specific open region of chromatin in peripheral blood mononuclear cells (PBMC) of breast cancer patients and explore its possibility as biomarkers for diagnosis and predicting prognosis of breast cancer. Methods: We obtained PBMCs from breast cancer patients and healthy population for ATAC-seq (n=3), and obtained GSE27562 chip sequencing data sequencing for secondary analysis. Through bioinformatics analysis, we mined the change pattern of chromatin accessibility in PBMC of breast cancer. Results: A total of 1906 differentially accessible regions (DAR) and 1632 differentially expressed genes (DEGs) were identified in ATAC sequencing. Upregulated DEG in the disease group is mainly distributed in cells, organelles and cell intima related structures, mainly performing biological functions such as cell nitrogen complex metabolism, macromolecular metabolism and cell communication, and also related to functions such as nucleic acid binding, enzyme binding, hydrolase reaction and transferase activity. Combined with the microarray data analysis, the latter set of nine DEGs showed intersection in ATAC and microarray data, including Jun, MSL 2, CDC42, TRIB 1, SERTAD3, RAB 14, RHOB, RAB40B, and PRKDC. HOMER predicted identified five transcription factors potentially binding to these Peak sites, including NFY, Sp 2, GFY, NRF, and ELK 1. Conclusion: Chromatin accessibility analysis of peripheral blood mononuclear cells in early breast cancer patients underscores its potential as a significant avenue for biomarker discovery in breast cancer diagnostics and treatment. By screening transcription factors and differentially expressed genes related to breast cancer, this research provides a comprehensive theoretical foundation that may guide future clinical applications and therapeutic developments.